“NGOBROL JELANTAH” KOMUNIKASI LINGKUNGAN PENDEKATAN SOSIAL-BUDAYA OLEH BANK JELANTAH SEKAR SEJAGAD 88 SEMARANG - Emanuela Agra Sarika Kurnia Dewi (Jurnal Komunikasi dan Media, 2024)
The amount of waste cooking oil in Indonesia is large due to dominance of food processing by frying has given rise to new environmental issues. Non-B3 waste originating from these households can be negative for both health and the environment. This is because used cooking oil cannot be disposed of directly in water or land withour processing, and also cannot be combined with other piles of waste. However, not many people understand the proper way to dispose and process waste cooking oil. Bank Jelantah Sekar Sejagad 88 practices environmental communication to convey the message of how to process waste cooking oil is converted into economic value. This research uses qualitative methods with interviews with managers and members of Bank Jelantah Sekar Sejagad 88. The delivery of environmental communication messages with socio-cultural approach, based on character of the target community, namely women who are married. Based on research, there are two main socio-cultural charactistics of the audience, namely togetherness and socialicing which in togethernees is the means of disseminating daily information. The second character is that trust is built through valid information with the support of the local government. Based on these characteristic, there are strategies for delivering messages namely “Ngobrol Jelantah”, Gethok Tular, dan top-down concept. With this message delivery strategy, it can increase awareness of targets as shown by the increase in the number of members of Bank Jelantah Sekar Sejagad 88. Based on discussion, it appears that including targets through community empowerment is the right step in building mutual understanding in delivering environmental communication message.